AGTR1 Inhibits the Progression of Lung Adenocarcinoma - Xiong L (Dove Medical Press, 2021)
Lecai Xiong,1 Yanhong Wei,2 Xiao Zhou,1 Peng Dai,1 Yi Cai,1 Xuefeng Zhou,1 Ming Xu,1 Jinping Zhao,1 Hexiao Tang1 1Department of Thoracic Surgery, Zhongnan Hospital of Wuhan University, Wuhan, 430071, People’s Republic of China; 2Department of Rheumatology and Immunology, Zhongnan Hospital, Wuhan University, Wuhan, 430071, People’s Republic of ChinaCorrespondence: Hexiao TangThe Department of Thoracic Surgery, Zhongnan Hospital of Wuhan University, Wuhan, 430071, People’s Republic of ChinaTel +86-15102723563Email thx1245@sina.comPurpose: The occurrence and development of lung adenocarcinoma (LUAD) are related to many factors. Multiple researches showed that the renin-angiotensin system (RAS) plays an important role in lung cancer. This research mainly focuses on angiotensin II receptor 1 (AT1R) encoding gene AGTR1, an important part of the RAS.Methods: We comprehensively evaluated the expression of AGTR1 in pan-cancer based on RNA sequencing data obtained from The Cancer Genome Atlas (TCGA). We explored the correlation of AGTR1 with clinicopathological features, prognosis and tumor microenvironment in LUAD. We also explored the mechanism through enrichment analysis and verified it with cell lines and tissue samples.Results: We found that AGTR1 was less expressed in most tumors and related to prognosis based on the TCGA database. To further explore its mechanism, we mainly focused on LUAD. Combined with the verification results in the GEO database, AGTR1 was associated with a better prognosis in LUAD. High expression of AGTR1 was associated with less lymph node metastasis (P=0.007) and MET mutation (P=0.019). High expression of AGTR1 was related to the anti-tumor immune microenvironment with high infiltration of B cells, myeloid dendritic cells, monocytes, and low infiltration of myeloid-derived suppressor cells (all P< 0.05). Enrichment analysis and in vitro verification results showed that AGTR1 was likely to play a role in LUAD through the PI3K/AKT3 pathway. Finally, we verified the above results through tissue samples and the construction of AGTR1 overexpressing cells.Conclusion: AGTR1 inhibits the progression of lung adenocarcinoma through the PI3K/AKT3 pathway.Keywords: AGTR1, tumor suppressor gene, TCGA, lung adenocarcinoma, AKT3